Gabapentin in Refractory Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The efficacy of gabapentin as an additional medication in 32 children with refractory partial seizures was studied at the Children's Hospital, Boston, MA.